Earnings Management, Leverage, Good Corporate Governance, And Tax Avoidance - Indriani, Sintiati; Ramli, Abdul Haeba (Jurnal Ilmiah Akuntansi Kesatuan, 2024)
The purpose of this research is to analyze the influence of earnings management, leverage and good corporate governance against tax avoidance. The sample used in this research is raw materials sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2019 until 2022. The population of this research is 97 companies in the raw materials sector. The sampling technique used is purposive sampling So the total sample used in this research was 16 companies in the raw materials sector. The design of this research is causality which looks for the influence of cause and effect relationships. The data analysis technique in this research uses multiple linear regression analysis. The results of the research indicate that partially the earnings management and good corporate governance has no effect on tax avoidance, while the variable leverage has a positive effect on tax avoidance. Earnings management variables, leverage, and good corporate governance simultaneously influences tax avoidance. Keywords: Earnings Management, Leverage, Good Corporate Governance, Tax Avoidance